PREFERENSI DAN TINGKAT KEPUASAN KONSUMEN BANANA CRISPY PADA DUA UMKM DI KECAMATAN GEDONG TATAAN - Hayatin Nufus; Wuryaningsih Dwi Sayekti; Rabiatul Adawiyah (Lampung University, 2022)
The research aims to study preference, consumer satisfaction, post-purchase behavior of banana crispy in two MSMEs at Gedong Tataan District. The research location was determined survey method in Banana Melted Lampung and Banana Monalisa. There are 45 respondents in this study who were taken by sampling quota. Data were collected in January-March 2022. Data of preferences and purchasing decisions were analyzed by descriptive quantitatively, while satisfaction level were analyzed using Customer Satisfaction Index (CSI). This research results indicated that consumers preferred banana crispy at Banana Melted Lampung than at Banana Monalisa. The level Customer Satisfaction Index (CSI) in consuming banana crispy at Banana Melted Lampung was in the very satisfied criteria, while at Banana Monalisa was in the satisfied criteria. The number of purchases of banana crispy in the two MSMEs is two boxes per month. In purchasing decisions, after consumers evaluate the product, 11 people still consume Banana Melted Lampung, then 10 consumers only consume Banana Monalisa, and the rest still consume both. Key words: Crispy banana, decision, preference, satisfaction.